Statistical Analysis and Effects of Radio Frequency Interference in GPS Signal Quality in Thailand - Somkit Sophan; Pornchai Supnithi; Lin M. M. Myint; Jirapoom Budtho; Susumu Saito (My University, 2024)
Abstract The radio frequency interference (RFI) in global navigation satellite system (GNSS) signals has recently received much attention in the GNSS community because of frequent jamming issues. The carrier-to-noise density ratio ( C/N 0 ) is one of the common parameters to indicate the signal quality. In this work, we aim to analyze the occurrences of local RFI effects in areas surrounding the Suvarnabhumi International Airport as well as remote areas. Specifically, the percentage of RFI levels and raw C/N 0 values are analyzed based on the modified RFI detection. The estimated RFI values are created from the raw C/N 0 data, followed by the RFI levels generated by the empirical data. We validate the modified RFI detection by using the GNSS reference stations at the urban, suburban, and outside the capital city in Thailand. The user positioning errors with the high (severe) RFI levels are investigated based on the single point positioning (SPP) and real-time kinematics (RTK). From the experimental simulations, the high RFI levels at the urban are higher than those at the suburban. As expected, the statistical analysis covering COVID-19 (2019 to 2023) shows that the high RFI levels in June 2023 (post COVID-19) are more than those in June 2020 and 2021 (lockdown COVID-19) about twofold. Additionally, the SPP and RTK errors with the medium/high RFI levels have the error spikes in the centimeter to meter levels. The RTK performance with the fixed status can be affected and then returned to the float status as well.
Keywords: Radio signal; SIGNAL (programming language); GNSS positioning and interference